Inventory Control Accounting Computerization In J-Mart Karawang Based On Vb.Net 2008 - Indaryono Indaryono; Donny Apdian; Dudi Awalludin; Intan Ayu Nurhasanah (Dirgamaya: Jurnal Manajemen dan Sistem Informasi, 2021)
When presented with an accounting information system based on a reliable system, it will certainly produce objective information as well. Inventory management and computerized goods reports are very beneficial for the company. J-Mart, which is a minimarket which still relies on Ms. So that data processing of reports cannot be fast and accurate. This study uses data collection methods in the form of observation, interviews and documentation. This application is designed to use Visual Basic.Net with SQL Server as the database. The output result obtained from this system is the inventory report. With the creation of this inventory system, it is hoped that it can make it easier to carry out the process of recording inventory, avoid input errors and can streamline the time of inputting and counting stock items in the warehouse.